2020
DOI: 10.1007/s40430-020-02550-9
|View full text |Cite
|
Sign up to set email alerts
|

In-plane and out-of-plane compressive mechanical properties of Nomex honeycombs and their prediction

Abstract: Based on experiments used to evaluate the in-plane and out-of-plane mechanical properties of Nomex honeycomb, the influences of different cell geometries and honeycomb densities on the mechanical properties of honeycombs were investigated. The content of each component of honeycomb was analysed by disassembly. Furthermore, by introducing the wall thickness ratio and a correction function, a theoretical prediction model of out-of-plane mechanical properties was constructed. As for the prediction of in-plane mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Using the super-folding method, the energy-absorption properties of origami designs honeycombs were theoretically determined. The accuracy of the proposed model was confirmed by the error between the numerical simulations and theoretical results, which ranged from -8.55% to 6.50% [29][30][31]. In this regard, the current research explored with the influences of cell parameters of honeycomb core reinforced using numerical analysis especially for out-of-plane structures.…”
Section: Introductionmentioning
confidence: 75%
“…Using the super-folding method, the energy-absorption properties of origami designs honeycombs were theoretically determined. The accuracy of the proposed model was confirmed by the error between the numerical simulations and theoretical results, which ranged from -8.55% to 6.50% [29][30][31]. In this regard, the current research explored with the influences of cell parameters of honeycomb core reinforced using numerical analysis especially for out-of-plane structures.…”
Section: Introductionmentioning
confidence: 75%
“…The flattened cell walls generally consist of two types of failure: buckling and crack for double-layered wall; fold and fracture for single-layered due to the adhesive failure (Figure 6(f) and (g)). 28 Figure 7 is a sketch showing the detailed deformation process. A local buckling appeared on the honeycomb cell walls (Figure 7(b)).…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…The flattened cell walls generally consist of two types of failure: buckling and crack for double-layered wall; fold and fracture for single-layered due to the adhesive failure (Figure 6(f) and (g)). 28…”
Section: Pbo Paper Honeycomb Cores-flatwise Compression Test Resultsmentioning
confidence: 99%
“…Compared to in-plane compression loading, out-of-plane compression loading leads to higher peak force and energy absorption in the honeycomb structure. 23,24 Extensive experimental research has unequivocally demonstrated the exceptional bearing capacity and energy absorption capabilities of Nomex honeycombs. Nevertheless, there is an imperative for continued exploration to unlock the full potential of Nomex honeycomb sandwich panels, driven by ever-increasing demands and requirements.…”
Section: Introductionmentioning
confidence: 99%